FALSAFAH PIIL PESENGGIRI SEBAGAI KEARIFAN KOTA LAMPUNG TERAKTUALISASI MELALUI PENDIDIKAN NON FORMAL - Fachruddin, Fachruddin (Perspektif Ilmu Pendidikan, 2007)
Many kinds of traditional value in Indonesia are useful for human life and some of the local traditional value can be adopted at national level. This article describes how PIIL Pesenggiri as a local value in Lampung could disseminate and only in Lampung itself but it can be adopted and developed in other regions. PIIL Pesenggiri will be taken as a way of life to create peaceful societies. Based on the experiences, PIIL Pesenggiri can be diffused widely through non formal education.